2017
DOI: 10.15376/biores.12.2.3918-3932
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Kinetics of Biochar Prepared by Pyrolysis of Macadamia Shells

Abstract: The use of macadamia shells (MSs) has become an active research direction because of increasing production. This paper considers the combustion characteristics of MSs and their biochars that were investigated with thermogravimetry analysis (TGA). Combustion thermographs were obtained at different heating rates, using isoconversional methods expressed by combustion kinetics. The Kissinger-Akahira-Sunose (KAS) method authenticated the MSs, MSs-300, and MSs-600 average activation energy at 91.6 kJ/mol, 60.5 kJ/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, studies on the energy utilization of MNS are rarely reported. In these respects, a related study has been conducted [ 13 , 14 ]. The results show that prepared biochar from MNS offers an important application prospect.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the energy utilization of MNS are rarely reported. In these respects, a related study has been conducted [ 13 , 14 ]. The results show that prepared biochar from MNS offers an important application prospect.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass pyrolysis technology is suitable for biomass carbonization because it considers the types, distribution characteristics, and economy of biomass resources, and the raw material of carbonization technology is mainly fruit shell waste. 28 Walnuts have a certain scale in the food processing industry. The output of walnut shells is large, unreasonably utilized, and treated as garbage, thereby subjecting these shells to incineration.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the weight loss rate at a given temperature point and the maximum rate of weight loss through pyrolysis increased in response to an increase in the heating rate; this nding is in agreement with the pyrolysis results of lees reported by Wang 56 et al, this is because the increased heat conduction between the sample and the reactor, which is induced by the accelerated heating rate, causes the interior of the lees to reach the maximum pyrolysis temperature more quickly when the pyrolysis process begins; volatile components precipitate rapidly, which in turn increases the rate at which weight is lost. 57,58 Analysis of pyrolysis kinetics of yellow wine lees…”
Section: Inuence Of Heating Rate On the Pyrolysis Process Of Yellow ...mentioning
confidence: 99%